COMPARING THE RESULTS OF SPINAL REHABILITATION BY THE CS-A15 EXERCISE PROGRAM WITH MC KENZIE EXERCISES IN PATIENTS WITH LUMBAR DISC HERNIATION - Nguyen Van Tuan,; Hoang Van Thang,; Do Thi Duyen, (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to compare the spinal rehabilitation results of the CS-A15 exercise program with the Mc Kenzie exercises in patients with lumbar disc herniation. Methods: Prospective interventional study, type of controlled clinical trial. Results: After two weeks of treatment: Pain reduction according to VAS scale, Lasègue angle score, Schober index and the Oswestry disability index (ODI) in the study group and control group all improved significantly compared to before treatment, different from p < 0.001. As for the ODI, the patients in the study group had a better improvement than the control group, the difference was statistically significant with p < 0.05. - After one month of treatment: Both the CS-A15 exercise program group and the Mc Kenzie exercises group reduced pain, reduced nerve root tension, improved spinal range of motion and the ODI, significantly different from before treatment, with p < 0.0001. Particularly in terms of pain relief, nerve root tension and the ODI, the patients in the study group had a better improvement than the control group patients, the difference was statistically significant with p < 0.05.